2017
DOI: 10.1002/14651858.cd008895.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Patient education in the management of coronary heart disease

Abstract: Cochrane Database of Systematic Reviews Data collection and analysis Two review authors independently screened all identified references for inclusion based on the above inclusion criteria. One author extracted study characteristics from the included trials and assessed their risk of bias; a second review author checked data. Two independent reviewers extracted outcome data onto a standardised collection form. For dichotomous variables, risk ratios and 95% confidence intervals (CI) were derived for each outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
3
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(170 citation statements)
references
References 202 publications
6
128
3
10
Order By: Relevance
“…One review suggested education improved quality of life in people with cardiac disease. 61 However, self-management by a patient with a long-term disabling condition depends on education, and there is evidence to support teaching selfmanagement strategies for:…”
Section: Education and Self-managementmentioning
confidence: 99%
“…One review suggested education improved quality of life in people with cardiac disease. 61 However, self-management by a patient with a long-term disabling condition depends on education, and there is evidence to support teaching selfmanagement strategies for:…”
Section: Education and Self-managementmentioning
confidence: 99%
“…The paper highlights that such education programs improve patient disease-specific knowledge and quality of life, and reduce respiratory-related hospital admissions and emergency department visits. Anderson et al (2017) focus on the educational component of cardiac rehabilitation for patients with coronary heart diseases. The study reviews 22 randomized control trials that assigned patients to different educational interventions that ranged from face-to-face counseling to residential stays with follow-up sessions.…”
Section: C4 Patient Educationmentioning
confidence: 99%
“…As mentioned previously, a key challenge relates to how to operationalise the concept of patient education. Within a research context, the Cochrane review definition 122 requires the presence of all four of the following elements: (1) instructional activities organised in a systematic way, (2) an inpatient, outpatient or community setting, (3) structured knowledge transfer about CHD for secondary prevention and (4) face to face (group or one to one) or interactive delivery.…”
Section: Intervention Componentsmentioning
confidence: 99%